Дослідження органів публічної адміністрації в системі суб'єктів дозвільної діяльності в Україні - Джафарова, О. В.; Dzhafarova, O. V.; Джафарова Олена В'ячеславівна (Форум права. - 2018. - № 1. - С. 42-49, 2018)
Підтримується широкий підхід до визначення категорії «органи публічної адміністрації» як системи органів державної, насамперед виконавчої, влади, органів місцевого самоврядування, інших суб'єктів, які з метою реалізації публічного інтересу відповідно до закону чи адміністративного договору наділяються делегованими повноваженнями у всіх сферах функціонування суспільства. Визначено систему органів публічної адміністрації, які є суб'єктами дозвільної діяльності. Досліджено органи публічної адміністрації як суб'єкти дозвільної діяльності, які беруть участь у реалізації державної політики у певних сферах розвитку суспільства.

The article states that the category of «subject of public administration» in its current meaning does not cover the whole range of subjects involved in the realization of public functions of the state. To date, it is extremely necessary to find a category that would unite all entities with public authority competence in line with the legislation of the European Union, as well as to maximize the needs of the practice of law enforcement. An extremely urgent task is to release the theory of administrative law from outdated terms and to fill it with categories that should correspond not only to the realities of Ukrainian life and the practice of state formation, but also to the legislation of the European Union as a prerequisite for the European integration of our state. A broad approach to the definition of the category of «public administration bodies» as a system of state bodies, primarily executive, authorities, local governments, and other entities that, in order to realize public interest in accordance with the law or administrative contract, are delegated with powers in all spheres of the functioning of society. The system of bodies of public administration, which are subjects of licensing activity, is defined, namely: 1) the Cabinet of Ministers of Ukraine; 2) central and local executive authorities; 2) executive bodies with special status; 3) bodies of state power without the status of a body of executive power; 4) collegial bodies of state power; 5) local self-government bodies represented by the executive committees of the respective councils; 6) legal entities of public law (enterprises, institutions, organizations); 7) legal entities of private law; 8) self-governing organizations. The bodies of public administration as subjects of licensing activity that are involved in the implementation of state policy in certain spheres of society development are investigated. This is done through an understanding of the purpose of the licensing activity, which is to ensure the life, health, safety of the environment, national interests and maintaining a balance of private and public interests.

Поддерживается широкий подход к определению категории «органы публичной администрации» как системы органов государственной, прежде всего исполнительной, власти, органов местного самоуправления, других субъектов, с целью реализации публичного интереса в соответствии с законом или административного договора наделяются делегированными полномочиями во всех сферах функционирования общества. Определена система органов публичной администрации, которые являются субъектами разрешительной деятельности. Исследованы органы публичной администрации как субъекты разрешительной деятельности, участвующих в реализации государственной политики в определенных сферах развития общества.
Study of Public Administration Bodies in the System of Subjects of Licensing Activity in Ukraine
Исследование органов публичной администрации в системе субъектов разрешительной деятельности в Украине
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; органи публічної адміністрації; теорія публічної адміністрації; дозвільна діяльність; суб'єкти дозвільної діяльності; органы публичной администрации; теория публичной администрации; разрешительная деятельность; субъекты разрешительной деятельности; bodies of public administration; public administration theory; permit activity; subject of leisure activities